2006
DOI: 10.1038/sj.bjp.0706469
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resveratrol, a phytoalexin derived from red wines, on chronic inflammation induced in an experimentally induced colitis model

Abstract: 1 Neutrophil infiltration, proinflammatory cytokines, eicosanoid generation and oxidative stress have been implicated in colitis. Resveratrol is a polyphenolic compound found in grapes and wine, with multiple pharmacological actions, including anti-inflammatory, antioxidant, antitumour and immunomodulatory activities. In a previous report, we documented that resveratrol decreases the degree of inflammation associated with acute experimental colonic inflammation, but its effects on chronic experimental colitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(143 citation statements)
references
References 55 publications
11
129
0
3
Order By: Relevance
“…Likewise, the upregulation of certain proteins, i.e. cyclo-oxygenase A c c e p t e d M a n u s c r i p t (COX)-2 and inducible nitric oxide synthase (iNOS) has also been implicated and considered important determinants of colonic damage [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the upregulation of certain proteins, i.e. cyclo-oxygenase A c c e p t e d M a n u s c r i p t (COX)-2 and inducible nitric oxide synthase (iNOS) has also been implicated and considered important determinants of colonic damage [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Basd on the inflammatory effects of TNF-alpha and resistin in the insulin receptor of the cells, clinical evidences [121] have shown that we can utilize also resveratrol (trans-5,3,4-trihydroxystilbene) against insulin resistance. Because this agent increases the activity of superoxide dismutase and glutathione peroxidase, and decreases the plasma levels of TNF-alpha, interferon-gamma, cyclooxygenase-2 (COX-2) and pro-inflammatory ILs [122][123][124]. Especially the plasma levels of TNF-alpha show a significant decrease [123,125] and so, resveratrol improves this dysfunction of insulin receptor caused by inflammatory adipokines.…”
Section: Insulin Resistance and Its Treatmentmentioning
confidence: 99%
“…1,2 Vários estudos têm destacado e comprovado os benefícios do resveratrol à saúde. Esta substância tem demonstrado propriedades quimiopreventivas, [3][4][5][6][7][8] antioxidante, 9,10 antiplaquetária, 11 antifúngica, 12 anti-inflamatória, 13 cardioprotetora, 14,15 entre outras. O resveratrol age como efetor biológico pleiotrópico que regula as três fases do processo da carcinogênese, ou seja, início, promoção e progressão do tumor.…”
Section: Introductionunclassified